Relationship between Service Quality and Customer Satisfaction - Abbas, Muhammad (Advances in Business & Industrial Marketing Research, 2023)
This research aims to measure customer satisfaction in service quality dimensions, namely physical evidence, reliability, responsiveness, assurance and empathy. The research method uses a questionnaire distributed to 65 Damri Bus passengers. After the results were obtained through the reliability and validity tests, they were analyzed using Multiple Linear Regression with the SPSS 17.0 for Windows program in which the classical assumption test, multicollinearity test, heteroscedasticity test, normality test, t-test, f test and coefficient of determination (R2) test were carried out. Based on the analysis, it is concluded that service quality (SERVQUAL) affects the level of customer satisfaction individually and simultaneously and is empirically proven. The dominant factor that most affects customer satisfaction on Damri Buses in Makassar City is physical evidence.